Utilisation of adequately Iodised salt and its determinants at household level among the tribal population of Yercaud hills in South India – A Community Based Cross Sectional Study - Shini Preetha Nirmalson; M. Vijayakarthikeyan; M.D. Thenmozhi (Global Journal of Medicine and Public Health, 2024)
Background Most cost effective and sustainable intervention to address iodine deficiency is the Universal Salt Iodization (USI). According to the National Family Health Survey 5 (NFHS 5) data, 94.3% of the households in India were consuming adequately Iodised salt. Objectives 1. To estimate the prevalence of Iodised salt utilisation at the household level using a Rapid Diagnostic Test (RDT). 2. To determine the factors influencing Iodised salt utilisation at the household level. 3. To estimate the Urinary Iodine Excretion (UIE) among the tribal population.